Cutaneous loxoscelism predominantly edematous: Clinical Case: Loxoscelismo cutáneo predominantemente edematoso : Caso Clinico - Luna-Muñoz, Consuelo (2022)
The spider bite of the genus Loxosceles is a public health problem in regions of Latin America. In Peru, it occurs more frequently in homes in the coastal region and could have serious consequences, including death in the case of cutaneous and visceral loxoscelism (CVL). The case of a pediatric patient with a suspected spider bite is presented below. The clinical picture developed with marked edema of the face and neck, without developing respiratory distress and without evidence of systemic compromise. The slow resolution of the edema and the lack of response to the treatment of choice for angioedema allowed us to guide the diagnosis to predominantly edematous cutaneous loxoscelism (CLEP), which is an infrequent form of presentation.